Naphthalimide-based Ligands in Metal Complexes: Bridging Structural Design and Biological Activity - Stjärnhage, J; Kitchen, JA; Hartinger, CG (Elsevier BV, 2026)
Metal complexes are a mainstay in cancer chemotherapy since the discovery of cisplatin and related metal complexes as highly effective anticancer agents. Interest in the development of other metal complexes has been driven by the various drawbacks of these agents including their off-target toxicity and tumour resistance. An important strategy towards development of new anticancer metal complexes is through incorporation of organic moieties which themselves have biological activity. Various organic compounds derived from 1,8-naphthalimide have found use in biological applications, with the core scaffold being highly fluorescent and intercalating DNA. As naphthalimide-based organic compounds have reached phase 2 clinical trials, considerable interest was prompted towards utilising the naphthalimide moiety in the design of bioactive metal complexes. Within this comprehensive review, we have collated and described the diverse range of biologically active metal complexes that have been reported which incorporate naphthalimide moieties. We discussed the impact of naphthalimide functionalisation on the biological properties of metal complexes while we critically examined the advantages and the shortcomings of the followed approaches.
Keywords: 3402 Inorganic Chemistry; 34 Chemical Sciences; Cancer; 0302 Inorganic Chemistry; 0306 Physical Chemistry (incl. Structural); 0399 Other Chemical Sciences; General Chemistry; 3402 Inorganic chemistry; 4003 Biomedical engineering